The “intraendothelial canalicular formation”: the route for lymphocyte diapedesis at the level of peripheral and mucosa-associated lymphoid tissue HEVs - Azzali, G.; Arcari, M.L.; Caldara et al., G.F. (Acta Biomedica Atenei Parmensis, 2010)
How the lymphocyte crosses the blood endothelium during transendothelial migration is demonstrated through the study of serial sections of high endothelial venules (HEVs) of peripheral (mesenteric lymph nodes) and mucosa-associated lymphoid tissue (Peyer’s patches, vermiform appendix) during normal lymphocyte homing and experimental intestinal inflammation. The sequence of serial ultrastructural features of lymphocytes englobed in the endothelial wall at different moments of transmigration made it possible to bring out that their transendothelial migration toward the extracellular matrix of lymphoid tissues occurs through an intraendothelial canalicular formation constituted by two adjacent endothelial cells that have closed interendothelial junctions. This intraendothelial canalicular formation, morphologically unlike the transcellular and paracellular migratory pathways, is an innovative model of migratory route for lymphocyte diapedesis that does not compromise the continuity of the endothelial wall. The increased presence of lymphocytes and intraendothelial canalicular formations during experimental inflammation and the metabolic hyperactivity of the spring/summer months compared to the lethargic fast in Chiropters underscores an influence on lymphocyte traffic through the HEVs of the peripheral and mucosa-associated lymphoid tissue.